2006
DOI: 10.1111/j.1399-3054.2006.00583.x
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of cDNAs encoding cell‐wall hydrolases from pear (Pyrus communis) fruit and their involvement in fruit softening and development of melting texture

Abstract: ‘La France’ pear (Pyrus communis L.) fruit stored at 1°C for 1 month (short‐term storage) before transfer to 20°C softened and developed a melting texture during ripening, whereas fruit stored for 5 months (long‐term storage) before transfer to 20°C softened but did not develop a melting texture. To clarify the mechanisms involved in fruit softening and textural changes, the cDNAs encoding cell‐wall hydrolases were isolated by RT‐PCR, and their expression and localization were investigated in ‘La France’ pears… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 42 publications
(45 reference statements)
2
18
0
1
Order By: Relevance
“…Presence of PYC-007 in two locations in the pear genome was confirmed by mapping to linkage groups 9 and 17 of an M27 9 M116 apple population (Felicidad Fernández-Fernández, personal communication). The dinucleotide motif in PYC-001 was found in the 3 0 UTR of the polygalacturonase PC-PG2, one of three PG enzymes isolated from pear (Sekine et al 2006). The forward primer of PYC-001 was designed from the coding region that is usually conserved in the three pear genes.…”
Section: Discussionmentioning
confidence: 99%
“…Presence of PYC-007 in two locations in the pear genome was confirmed by mapping to linkage groups 9 and 17 of an M27 9 M116 apple population (Felicidad Fernández-Fernández, personal communication). The dinucleotide motif in PYC-001 was found in the 3 0 UTR of the polygalacturonase PC-PG2, one of three PG enzymes isolated from pear (Sekine et al 2006). The forward primer of PYC-001 was designed from the coding region that is usually conserved in the three pear genes.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, PGs involved in fleshy fruit ripening, such as the tomato (TFPG), grape (VvPG1), apple (MdPG1), kiwi (CkPGA3) and pear (PcPG1) are also found within this clade [23,25-27,36,43,44,48,50,51]. In addition, only the melon PG (CmPG3) that has an expression profile related to ripening is found in the same subclade as the dry fruit dehiscence and abscission PGs, while the other two melon PGs (CmPG1 and CmPG2) associated with organ abscission and ripening are in the same subclade as EgPG4 [19].…”
Section: Discussionmentioning
confidence: 99%
“…At least seven β-galactosidase genes are expressed during development and ripening of tomato fruit (Smith and Gross, 2000). A family of β-galactosidase was also reported in strawberry (Trainotti et al, 2001), Japanese pear (Tateishi et al, 2001b(Tateishi et al, , 2005b, avocado (Tateishi et al, 2002(Tateishi et al, , 2007, pear (Pyrus communis) (Mwaniki et al, 2005(Mwaniki et al, , 2007Sekine et al, 2006), and grape (Vitis vinifera) (Nunan et al, 2001). Some gene expressions overlapped.…”
Section: Genes For β-Galactosidasementioning
confidence: 98%
“…Itai et al (2003) reported that family 51 α-L-arabinofuranosidase cloned from tomato fruit were expressed during fruit development and declined during ripening. Sekine et al (2006) reported that family 51 α-L-arabinofuranosidase cloned from pear fruit was expressed constitutively during fruit storage. From only expression analysis of family 51 α-L-arabinofuranosidase, it seems to contribute less to fruit softening, but its detailed role in physiological metabolism remains unclear.…”
Section: Expression Pattern Of α-L-arabinofuranosidasesmentioning
confidence: 99%